Non-randomised study comparing toxicity of Escherichia coli and Erwinia asparaginase in children with leukaemia. - Eden, O; Shaw, M; Lilleyman, J; Richards, S (1990)
Seven hundred fifty-eight unselected children entered into the United Kingdom Medical Research Council acute lymphoblastic leukaemia UKALL VIII Study and Trial were studied for differences in early treatment-related toxicity according to the type of intramuscular L-asparaginase received. Two hundred seventy-five received a product obtained from Escherichia coli and 483 the enzyme from Erwinia chrysanthemi. The E. coli patients had a significantly higher incidence of neurotoxicity, pancreatitis, and life-threatening sepsis (4%, 2%, and 20%, respectively) when compared with the Erwinia group (2%, 0%, and 18%). Severe hypersensitivity was seen in one patient from both groups and the incidence of glucose intolerance was not significantly different. These findings indicate that E. coli asparaginase may be more toxic. With a minimum follow up of 4 1/2 years there is no evidence that either product has made a significantly different contribution to disease-free survival.